Effect of Elastomeric Bearing Stiffness on the Dynamic Response of Railway Bridges Considering Vehicle–Bridge Interaction - Emrah Erduran; Christian Nordli; Semih Gonen (Applied Sciences, 2022)
This article presents a numerical study that aims to explore the impacts of the stiffness of elastomeric bearings on the dynamic behavior of railway bridges under train-induced vibrations. For this purpose, a finite element code that considers vehicle–bridge interaction using a coupled approach was developed. The software was validated by comparing the numerical response to the analytical solution. The numerical analysis of single- and multi-span bridges with varying bearing stiffness values under passenger trains showed the interplay between bearing stiffness, its impact on the natural frequency of the bridge and the loading frequency. It is demonstrated that the amplitude of the maximum acceleration on the bridge depends heavily on the stiffness of the bearings. Furthermore, the bearing stiffness significantly impacts the location of the maximum acceleration on the bridge. The results of the extensive numerical analyses improve the understanding of the impact of the bearing stiffness on the dynamic behavior of bridges and highlight the importance of quantifying the boundary conditions correctly for reliable estimation of dynamic response of railway bridges under train-induced vibrations.